A Study on Sandstone Damage Model Based on the Correlation Between Energy Dissipation and Plastic Strain - Tianbai Zhou; Xiaoyu Zhang; Yongbo Cai; Long Wang; Qixian Li (Applied Sciences)
The process of rock damage and failure is accompanied by the dissipation of energy and an increase in plastic strain. This study attempts to determine the relationship between dissipated energy and plastic strain in sandstone during the damage and failure process. A conventional triaxial cyclic loading and unloading test was conducted on sandstone samples to analyze the energy evolution and plastic strain characteristics of rock during the mechanical performance degradation and deformation failure process. The analysis results indicate that the evolution law of rock energy dissipation and plastic growth during the whole stress–strain process is highly consistent. Before the peak stress, dissipated energy and plastic strain increased linearly with input energy and axial strain, respectively. In the residual stress stage, there is an approximate linear evolution relationship between dissipated energy and plastic strain. Based on the correlation characteristics of energy dissipation and plastic growth, a modified damage model was established by characterizing plastic deformation by damage. In addition, a numerical program was developed using the Finite Volume Method (FVM) based on the damage model. The rock damage model has been validated by experimental results and numerical test. The research findings may provide valuable insights into the correlation mechanism between energy dissipation and plastic growth.